Isolation and purification of a novel antimicrobial peptide from Porphyra yezoensis. Issue 7 (29th April 2019) - Jiao, Kui; Gao, Jie; Zhou, Tao; Yu, Jia; Song, Huiping; Wei, Yuxi; Gao, Xiang
Abstract: We aimed to isolate antimicrobial peptides from Porphyra yezoensis . Enzymatic hydrolysate of P. yezoensis was purified by ultrafiltration, molecular sieve chromatography, and ion exchange chromatography sequentially. A novel peptide with strong antimicrobial activity against Staphylococcus aureus was isolated and the amino acid sequence was identified to be Thr‐Pro‐Asp‐Ser‐Glu‐Ala‐Leu (TPDSEAL). Physical and chemical properties and antimicrobial activity of the peptide were determined. The antimicrobial mechanism was studied. The antimicrobial activity of TPDSEAL kept stable under acidic or basic conditions, high temperature, and ultraviolet radiation. The antimicrobial mechanism of antimicrobial peptides may damage the cell wall and membrane, and enhance the permeability of cells, which leads to the outflow of intracellular substances and death of bacteria. This study provides novel insight into the preparation of marine‐derived antimicrobial peptides. Practical applications: Antimicrobial peptides, which act as defensive weapons against microbes, have been broadly used as food additives in food industry. Due to the limited amount of natural antimicrobial peptides in organisms and the high cost of chemical synthesis, producing novel natural antimicrobial peptides with bioengineering methods has become an urgent task. In the present study, we prepared a novel antimicrobial peptide from pepsin‐digested hydrolysate of Porphyra yezoensis using ultrafiltration, molecular sieve chromatography, ion exchange chromatography, and mass spectrometry analysis. A novel peptide with strong antimicrobial activity against Staphylococcus aureus was isolated and the amino acid sequence was identified to be Thr‐Pro‐Asp‐Ser‐Glu‐Ala‐Leu (TPDSEAL). The identified peptide exhibits great stability under acidic or basic conditions, high temperature, and ultraviolet radiation. Mechanism revealed that TPDSEAL treatment may damage the cell wall and membrane, enhance the permeability of cells, and lead to the death of bacteria. Our study provides the novel insight into the preparation of marine‐derived antimicrobial peptides.